Residual oil derived carbon supported Pt-Co-Au intermetallic compound as well as preparation method and application thereof

By using petroleum reduced pressure residue oil as a carbon support, residual oil-derived carbon-backed Pt-Co-Au intermetallic compounds with high metal loading, dispersion and excellent ORR catalytic activity were prepared, which solved the problems of particle agglomeration and easy dissolution of 3d transition metals during high-temperature calcination of existing catalysts, and significantly improved the performance and life of fuel cells.

CN119864435APending Publication Date: 2025-04-22BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311362875.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing high metal load IMC catalysts are prone to particle agglomeration during high temperature calcination, resulting in larger particle sizes and 3d transition metals are easily dissolution, which affects the long-term cycle activity and stability of the catalyst.

Method used

Petroleum reduced pressure residue oil was used as a carbon support and nitrogen doping and high temperature calcination treatment to prepare residual oil-derived carbon-backed Pt-Co-Au intermetallic compounds with high metal loading, dispersion and excellent ORR catalytic activity.

Benefits of technology

High metal loading, dispersion and excellent ORR catalytic activity are achieved, which significantly improves the performance and life of the fuel cell. The particles are evenly distributed under high temperature conditions and there is no obvious agglomeration phenomenon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864435A_ABST
    Figure CN119864435A_ABST
Patent Text Reader

Abstract

The invention discloses a residual oil derived carbon supported Pt-Co-Au intermetallic compound as well as a preparation method and application thereof. According to the preparation method, residual oil is used as a carbon source, nitrogen-doped petroleum vacuum residual oil porous carbon is synthesized through a template method and nitrogen doping modification, and the high-dispersion intermetallic compound composite material Pt-Co-Au / NPPC is prepared with the porous carbon material as a carrier through an impregnation reduction method. In the catalyst, the total metal loading capacity is 30 to 50 percent by weight, the Pt loading capacity is 26 to 41 percent by weight, the Co loading capacity is 3.8 to 7 percent by weight, and the Au loading capacity is 0.2 to 2 percent by weight. The residual oil derived carbon supported Pt-Co-Au composite material nano catalyst prepared by the invention has efficient oxygen reduction (ORR) catalytic activity, and the synthesized catalyst has the characteristic of small size. The small size can effectively improve the utilization rate of Pt atoms, and the doping of Au can optimize the electronic structure of surface Pt, so that the ORR activity is improved. The fuel cell membrane electrode test peak power density of the prepared catalyst under the hydrogen-air condition reaches 1.12 W / cm < 2 >, the synthesis steps are simple, and the catalyst has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a residual oil-derived carbon-supported Pt-Co-Au intermetallic compound and a preparation method thereof, and application thereof in oxygen reduction reactions and cathode catalysts of proton exchange membrane fuel cells. Background Art

[0002] The popularization of hydrogen fuel cell vehicles requires highly active and long-durable electrocatalysts. Platinum catalysts have been used in many scenarios, but the amount of platinum used in PEMFC is still very high. Platinum-based intermetallic compounds (IMCs) are considered to be the most promising catalysts for ORR because of their characteristics of improving the activity, atomic utilization and stability of platinum.

[0003] High metal loading IMC catalysts are believed to have great advantages for the application in actual fuel cell working conditions, making the catalyst layer (CL) thinner, which is beneficial to reduce mass transfer resistance, thereby improving the performance of the fuel cell. High metal loading can effectively alleviate the risk of carbon corrosion in fuel cells under actual working conditions, thus helping to extend the life of the fuel cell. However, high-loaded IMC catalysts still have the problem of difficulty in achieving high loading and particle agglomeration during high-temperature calcination, resulting in larger particle size.

[0004] At present, there are reports that the activity of intermetallic compounds can be increased by introducing a third element (such as Cu, Ni, Co...), but 3d transition metals are easily soluble, which affects the activity and stability of the catalyst in long-term cycles. In addition, the stability of the catalyst can be improved by introducing Au elements. The introduction of Au will further regulate the electronic structure of Pt, thereby improving the activity of the catalyst.

[0005] Petroleum vacuum residue is rich in carbon elements and aromatic groups, and can be used as a carbon source for various carbon nanomaterials. Their high carbon content and multifunctional adjustability can be used in various fields of electrochemistry, for example, as electrode materials for lithium-ion batteries, sodium-ion batteries and supercapacitors. However, there are few reports on the use of petroleum vacuum residue as a carrier to load high metal-loaded catalysts for fuel cells. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a residual oil-derived carbon-supported Pt-Co-Au intermetallic compound and a preparation method thereof. The residual oil-derived carbon-supported Pt-Co-Au intermetallic compound provided by the present invention has the characteristics of high metal loading, high dispersion and excellent ORR catalytic activity, and shows good working condition practicality in the membrane electrode test of proton exchange membrane fuel cell.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] The present invention provides a Pt-Co-Au intermetallic compound supported on residual oil-derived carbon, comprising: nitrogen-doped petroleum vacuum residual oil porous carbon; a ternary intermetallic compound supported on the surface of the nitrogen-doped petroleum vacuum residual oil porous carbon carrier; the ternary intermetallic compound is Pt-Co-Au. The active substance of the ternary intermetallic compound Pt-Co-Au is platinum cobalt gold nanoparticles, the average particle size of the particles is 3 to 6 nm, and the metal loading in the catalyst is 30 to 50 wt%, the Pt loading is 26 to 41 wt%, the Co loading is 3.8 to 7 wt%, and the Au loading is 0.2 to 2 wt%. The catalyst pore type is mesopore; the mesopore size is 30 to 40 nm, and the specific surface area is 600 to 800 m 2 / g.

[0009] The present invention also provides a method for preparing a residual oil-derived carbon-supported Pt-Co-Au intermetallic compound, comprising the following steps:

[0010] A. Disperse petroleum vacuum residue oil and nano-iron oxide in petroleum ether at a mass ratio of 1:4 to 1:6, stir thoroughly and dry to obtain a solid mixture. In an argon or nitrogen atmosphere, heat to 700-900°C at a rate of 5°C / min and keep warm for 100-150 minutes. Use 2mol / L hydrochloric acid to etch and remove the nano-iron oxide template, centrifuge, wash, dry and grind to obtain a porous carbon material of petroleum vacuum residue oil; dissolve the porous carbon material and urea in anhydrous ethanol and deionized water respectively, mix and stir, dry and grind, and obtain nitrogen-doped petroleum vacuum residue oil porous carbon after high-temperature calcination at 700-900°C for 100-150 minutes;

[0011] B. Nitrogen-doped petroleum vacuum residue porous carbon, hexahydrate chloroplatinic acid, hexahydrate chloroauric acid and hexahydrate cobalt chloride are dispersed in deionized water and ultrasonically mixed, and then dried to obtain an initial mixture; the initial mixture is reacted in an atmosphere of 5% hydrogen / 95% argon, firstly reduced at 150-300°C for 1-3h, with a heating rate of 2-10°C / min; then the temperature is continued to rise to 600-800°C and calcined for 0.5-2h, with a heating rate of 2-10°C / min; and the residue oil-derived carbon-supported Pt-Co-Au intermetallic compound is obtained. The above process mainly involves the reduction of Pt-based salts first, and then the reduction of other metal salts. Metal atoms move at high temperatures to obtain an ordered structure, and finally an ordered intermetallic compound is obtained; if the temperature is too high, the intermetallic compound particles will become larger; if the temperature is too low, only a disordered alloy can be obtained.

[0012] C. The obtained intermetallic compound catalyst is placed in 0.2-1.0 mol / L H2SO4 and etched for 4-6 hours to obtain the final product Pt-Co-Au / NPPC.

[0013] Furthermore, in step A, the mass concentration of the petroleum ether solution of the petroleum vacuum residue is 0.05-0.07 g / mL, the mass concentration of the petroleum ether solution of the template agent is 0.2-0.4 g / mL; the mass concentration of the urea aqueous solution is 0.14-0.42 g / mL; and the mass ratio of the carbon source to the nitrogen source is 1:3-1:7.

[0014] In this application, a porous carbon carrier with a large specific surface area is synthesized using petroleum vacuum residue. The large specific surface area provides more sites for the loading of metal particles to achieve a high metal loading; the nitrogen element is introduced to utilize its anchoring effect on the metal particles and the confinement effect of the mesopores to achieve the high dispersion characteristics of the metal particles, which is conducive to the synthesis of small-sized nanoparticles; gold is doped into the metal lattice to obtain an intermetallic compound, which optimizes the electronic structure of the platinum surface and improves the activity and stability of the catalyst; the above strategies can ultimately obtain the expected high-loading, highly dispersed ternary intermetallic compound Pt-Co-Au. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a high resolution transmission electron microscopy (HRTEM) image of the catalyst prepared in Example 1 of the present invention.

[0016] Figure 2 This is a statistical distribution diagram of the particle size of the catalyst prepared in Example 1 of the present invention.

[0017] Figure 3 This is a comparison chart of X-ray diffraction (XRD) of the catalysts prepared in Example 1 and Example 4 of the present invention.

[0018] Figure 4 This is a comparison chart of X-ray photoelectron spectroscopy (XPS) of the catalysts prepared in Example 1 and Example 4 of the present invention.

[0019] Figure 5 The spherical aberration corrected transmission electron microscope (HAADF-STEM) image and particle line scan image of the catalyst prepared in Example 1 of the present invention.

[0020] Figure 6 Cyclic voltammetry (CV) and linear polarization curves (LSV) of the catalysts prepared in Examples 1 and 4 of the present invention and commercial Pt / C.

[0021] Figure 7 This is a bar chart comparing the mass activity (MA) and specific activity (SA) of the catalysts prepared in Examples 1 and 4 of the present invention and commercial Pt / C.

[0022] Figure 8 Cyclic voltammetry (CV) and linear polarization curve (LSV) of the catalyst prepared in Example 1 of the present invention at the initial stage and after 30,000 cycles of stability testing.

[0023] Fig. 9 MA column comparison chart of the catalysts prepared in Example 1 and Example 4 of the present invention and commercial Pt / C at the initial and after 30,000 cycles of stability testing.

[0024] Fig.10 The fuel cell membrane electrode test diagram is for the catalysts prepared in Examples 1 and 4 of the present invention and commercial Pt / C.

[0025] Test method: The prepared catalyst ink was sprayed on the proton exchange membrane (5cm×5cm, DuPont 211 membrane), and the carbon paper (gas diffusion layer) was pressed with the proton exchange membrane coated with the catalyst at a certain pressure and temperature to prepare a membrane electrode assembly. The anode was sprayed with JM 60wt% commercial Pt / C, and the cathode was sprayed with the catalyst prepared in Example 1. The Pt loading of the cathode spray was 0.2mg / cm 2 The Pt loading of the anode spraying is 0.1 mg / cm 2 The test back pressure was 2 bar, the test temperature was 80°C, H2 with a humidity of 100% and air were introduced into the anode and cathode, respectively, and the gas flow rates were 400 mL / min and 1500 mL / min, respectively. DETAILED DESCRIPTION

[0026] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. Obviously, the described examples are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] (1) Mix 2.5g of petroleum vacuum residue and 12.5g of nano-iron oxide and disperse them in 40mL of petroleum ether and stir them mechanically for 6h at a stirring rate of 800rpm. After stirring, remove the solvent by rotary evaporation to obtain a uniform mixture; transfer the obtained mixture to a porcelain boat and place it in a tube furnace, introduce nitrogen as a protective gas, heat the tube furnace to 800℃ at a rate of 5℃ / min, and calcine for 120min; then naturally cool to room temperature and maintain normal pressure in the tube furnace; then transfer the obtained powder to a beaker, add 150mL of 2mol / L hydrochloric acid solution, stir for 12h, and perform acid etching; finally, centrifuge, wash and dry to obtain stone Petroleum vacuum residue porous carbon; 0.3 g of petroleum vacuum residue porous carbon and 1.5 g of urea are dissolved in 20 mL of ethanol and 20 mL of deionized water, respectively, and the mixture is dried and ground after being fully stirred; the obtained mixture is transferred to a porcelain boat and placed in a tubular furnace, and then nitrogen is introduced as a protective gas, and the tubular furnace is heated to 800 ° C at a rate of 5 ° C / min for nitrogen doping, and calcined for 120 min; then it is naturally cooled to room temperature, and the tubular furnace is maintained at normal pressure to obtain nitrogen-doped petroleum vacuum residue porous carbon;

[0029] (2) 54 mg of the obtained nitrogen-doped petroleum vacuum residue porous carbon, 93.0 mg of H2PtCl6·6H2O, 42.4 mg of CoCl2·6H2O and 1.05 mg of HAuCI4·4H2O were dispersed in 20 mL of deionized water and ultrasonically dispersed for 1 hour. After rotary evaporation and drying, a uniformly mixed precursor was obtained; the precursor was placed in a tubular furnace, argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tubular furnace as a protective gas, the tubular furnace was heated to 200°C at a rate of 5°C / min for reduction for 2 hours, and then the temperature was raised to 700°C at a rate of 5°C / min for calcination for 1 hour; finally, the temperature was naturally cooled to room temperature, and the tubular furnace was maintained at normal pressure to obtain an intermetallic compound catalyst.

[0030] (3) The obtained intermetallic compound catalyst is placed in 0.5 mol / L H2SO4 and etched for 5 h to obtain the final product, the residual oil-derived carbon-supported ternary intermetallic compound Pt-Co-Au.

[0031] from Figure 1 It can be seen that HRTEM shows that the Pt (111) interplanar spacing is 0.219nm, while the pure Pt (111) interplanar spacing is 0.227nm, which means that lattice compression occurs, and the particles are evenly distributed without obvious agglomeration, and the particle size is small. Figure 2 The particle size distribution diagram shows that the average particle size of the catalyst is 4.15±0.1nm, which is consistent with Figure 1 The distribution of particles corresponds well. Figure 3It shows that compared with Pt-Co / NPPC, the diffraction peak corresponding to the Pt(111) crystal plane in the XRD diagram of the ternary intermetallic compound Pt-Co-Au / NPPC shifts to a negative angle of 0.25°, indicating that Au is doped into the lattice, and Figure 4 The XPS spectrum shows that the Pt 4f 5 / 2 The binding energy of the peak is negatively shifted by 0.1 eV, which also indicates that Au enters the Pt lattice. Figure 1 and Figure 3 The XPS graph of Pt-Co-Au / NPPC shows obvious Au element peaks, which further proves the existence of Au. Figure 5 The spherical aberration electron microscope line scan shows the location of the Au element, which is distributed throughout the particle. Figure 6 and Figure 7 Among them, Pt-Co-Au / NPPC showed excellent ORR activity with MA of 0.924A / mg Pt , SA is 1.502mA / cm 2 . Figure 8 and Fig. 9 Among them, Pt-Co-Au / NPPC showed good durability, with only 22% loss of MA after 30,000 cycles. Fig.10 The results show that the peak power density of the membrane electrode test of the catalyst prepared by the present invention under hydrogen-air conditions reaches 1.12 W / cm 2 , the current density at 0.65V reaches 1.20A / cm 2 . It has good prospects for the industrial application of fuel cell catalysts.

[0032] Example 2

[0033] (1) Mix 2.5g of petroleum vacuum residue and 10.0g of nano-iron oxide and disperse them in 40mL of petroleum ether and stir mechanically for 6h at a stirring rate of 800rpm. After stirring, remove the solvent by rotary evaporation to obtain a uniform mixture; transfer the obtained mixture to a porcelain boat and place it in a tube furnace, introduce nitrogen as a protective gas, heat the tube furnace to 700℃ at a rate of 5℃ / min, and calcine for 100min; then naturally cool to room temperature, and maintain normal pressure in the tube furnace; then transfer the obtained powder to a beaker, add 150mL of 2mol / L hydrochloric acid solution, stir for 12h, and perform acid etching; finally, centrifuge, wash and dry to obtain stone Petroleum vacuum residue porous carbon; 0.3 g of petroleum vacuum residue porous carbon and 0.9 g of urea are dissolved in 20 mL of ethanol and 20 mL of deionized water, respectively, and the mixture is dried and ground after being fully stirred; the obtained mixture is transferred to a porcelain boat and placed in a tubular furnace, and then nitrogen is introduced as a protective gas, and the tubular furnace is heated to 700 ° C at a rate of 5 ° C / min for nitrogen doping, and calcined for 100 min; then the temperature is naturally reduced to room temperature, and the tubular furnace is maintained at normal pressure to obtain nitrogen-doped petroleum vacuum residue porous carbon;

[0034] (2) 65.9 mg of the obtained nitrogen-doped petroleum vacuum residue porous carbon, 69.1 mg of H2PtCl6·6H2O, 31.9 mg of CoCl2·6H2O and 0.42 mg of HAuCI4·4H2O were dispersed in 20 mL of deionized water and ultrasonically dispersed for 1 hour. After rotary evaporation and drying, a uniformly mixed precursor was obtained; the precursor was placed in a tubular furnace, and argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tubular furnace as a protective gas. The tubular furnace was heated to 150°C at a rate of 2°C / min for reduction for 1 hour, and then the temperature was increased to 600°C at a rate of 2°C / min for calcination for 0.5 hour; finally, the temperature was naturally cooled to room temperature, and the tubular furnace was maintained at normal pressure to obtain an intermetallic compound catalyst.

[0035] (3) The obtained intermetallic compound catalyst is placed in 0.2 mol / L H2SO4 and etched for 4 h to obtain the final product, the residual oil-derived carbon-supported ternary intermetallic compound Pt-Co-Au.

[0036] Example 3

[0037] (1) Mix 2.5g of petroleum vacuum residue and 15.0g of nano-iron oxide and disperse them in 40mL of petroleum ether and stir mechanically for 6h at a stirring rate of 800rpm. After stirring, remove the solvent by rotary evaporation to obtain a uniform mixture; transfer the obtained mixture to a porcelain boat and place it in a tube furnace, introduce nitrogen as a protective gas, heat the tube furnace to 900℃ at a rate of 5℃ / min, and calcine for 150min; then naturally cool to room temperature and maintain normal pressure in the tube furnace; then transfer the obtained powder to a beaker, add 150mL of 2mol / L hydrochloric acid solution, stir for 12h, and perform acid etching; finally, centrifuge, wash and dry to obtain stone Petroleum vacuum residue porous carbon; 0.3 g of petroleum vacuum residue porous carbon and 2.1 g of urea are dissolved in 20 mL of ethanol and 20 mL of deionized water, respectively, and the mixture is dried and ground after being fully stirred; the obtained mixture is transferred to a porcelain boat and placed in a tubular furnace, and then nitrogen is introduced as a protective gas, and the tubular furnace is heated to 900 ° C at a rate of 5 ° C / min for nitrogen doping, and calcined for 150 min; then it is naturally cooled to room temperature, and the tubular furnace is maintained at normal pressure to obtain nitrogen-doped petroleum vacuum residue porous carbon;

[0038] (2) 46.0 mg of mixed petroleum vacuum residue porous carbon, 106.3 mg of H2PtCl6·6H2O, 48.4 mg of CoCl2·6H2O and 4.2 mg of HAuCI4·4H2O were dispersed in 20 mL of deionized water and ultrasonically dispersed for 1 h. After rotary evaporation and drying, a uniformly mixed precursor was obtained. The precursor was placed in a tubular furnace, and argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tubular furnace as a protective gas. The tubular furnace was heated to 300°C at a rate of 10°C / min for reduction for 3 h, and then heated to 800°C at a rate of 10°C / min for calcination for 2 h. Finally, the temperature was naturally cooled to room temperature, and the tubular furnace was maintained at normal pressure to obtain an intermetallic compound catalyst.

[0039] (3) The obtained intermetallic compound catalyst is placed in 1.0 mol / L H2SO4 and etched for 6 h to obtain the final product, the residual oil-derived carbon-supported ternary intermetallic compound Pt-Co-Au.

[0040] Example 4

[0041] (1) 2.5 g of petroleum vacuum residue and 12.5 g of nano-iron oxide were mixed and dispersed in 40 mL of petroleum ether and mechanically stirred for 6 h at a stirring rate of 800 rpm. After stirring, the solvent was removed by rotary evaporation to obtain a uniform mixture; the obtained mixture was transferred to a porcelain boat and placed in a tube furnace, nitrogen was introduced as a protective gas, the tube furnace was heated to 800 ° C at a rate of 5 ° C / min, and calcined for 120 min; then it was naturally cooled to room temperature and the tube furnace was maintained at normal pressure; then the obtained powder was transferred to a beaker, a volume of 150 mL of a 2 mol / L hydrochloric acid solution was added, stirred for 12 h, and acid etching was performed; finally, centrifugation, washing and drying were performed to obtain petroleum Vacuum residue oil-based porous carbon; 0.3 g of petroleum vacuum residue oil porous carbon and 1.5 g of urea were dissolved in 20 mL of ethanol and 20 mL of deionized water, respectively, and the mixture was dried and ground after being fully stirred; the obtained mixture was transferred to a porcelain boat and placed in a tube furnace, and then nitrogen was introduced as a protective gas, and the tube furnace was heated to 800 ° C at a rate of 5 ° C / min for nitrogen doping, and calcined for 120 min; then it was naturally cooled to room temperature, and the tube furnace was maintained at normal pressure to obtain nitrogen-doped petroleum vacuum residue oil porous carbon;

[0042] (2) 54.5 mg of the obtained nitrogen-doped petroleum vacuum residue porous carbon, 93.0 mg of H2PtCl6·6H2O and 42.4 mg of CoCl2·6H2O were dispersed in 20 mL of deionized water and ultrasonically dispersed for 1 hour. After rotary evaporation and drying, a uniformly mixed precursor was obtained; the precursor was placed in a tubular furnace, argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tubular furnace as a protective gas, the tubular furnace was heated to 200°C at a rate of 5°C / min for reduction for 2 hours, and then the temperature was increased to 700°C at a rate of 5°C / min for calcination for 1 hour; finally, the temperature was naturally cooled to room temperature, and the tubular furnace was maintained at normal pressure to obtain an intermetallic compound catalyst.

[0043] (3) The obtained intermetallic compound catalyst is placed in 0.5 mol / L H2SO4 and etched for 5 h to obtain the final product, the residual oil-derived carbon-supported intermetallic compound Pt-Co.

Claims

1. A residual oil-derived carbon-supported Pt-Co-Au intermetallic compound, comprising: Nitrogen doped petroleum vacuum residue porous carbon; A ternary intermetallic compound supported on the surface of the nitrogen-doped petroleum vacuum residue porous carbon carrier; The ternary intermetallic compound is Pt-Co-Au.

2. The nitrogen-doped petroleum vacuum residue porous carbon-supported ternary intermetallic compound according to claim 1, characterized in that: The active substance of the ternary metal compound is platinum-cobalt-gold nanoparticles, the average particle size of the particles is 3-6nm, and the metal loading in the catalyst is 30-50wt%, the Pt loading is 26-41wt%, the Co loading is 3.8-7wt%, and the Au loading is 0.2-2wt%.

3. The nitrogen-doped petroleum vacuum residue porous carbon according to claim 1, characterized in that: The pore type is mesopore; the mesopore size is 30-40 nm, and the specific surface area is 600-800 m 2 / g.

4. A residual oil derived carbon supported Pt-Co-Au intermetallic compound as claimed in claim 1, comprising the following steps: (1) mixing nitrogen-doped petroleum vacuum residue porous carbon, a metal salt precursor and a solvent, and drying to obtain a mixture; the metal salt precursor is chloroplatinic acid hexahydrate, cobalt chloride hexahydrate and chloroauric acid hexahydrate; (2) heat treating the mixture in step (1) under a reducing atmosphere to obtain a ternary intermetallic compound composite material; the heat treatment process is firstly kept at 150-300° C. for 1-3 h, and then calcined at 600-800° C. for 0.5-2 h; the heating rate during the heat treatment process is 2-10° C. / min; (3) Etching the ternary intermetallic compound composite material of step (2) in sulfuric acid to obtain the final product Pt-Co-Au / NPPC; the sulfuric acid concentration is 0.2-1.0 mol / L; and the etching time is 4-6 h.

5. The preparation method according to claim 4, characterized in that: The specific preparation method of the nitrogen-doped petroleum vacuum residue porous carbon in step (1) is as follows: petroleum vacuum residue and template agent nano iron oxide are mixed in petroleum ether, mechanically stirred and then rotary evaporated, and the dried sample is pre-annealed to obtain a carbon material; the carbon material is placed in hydrochloric acid for etching, and then rotated, centrifuged and dried to obtain porous carbon; the porous carbon is mixed with urea and then calcined at high temperature to obtain nitrogen-doped petroleum vacuum residue porous carbon.

6. The preparation method according to claim 5, characterized in that: The concentration of the petroleum ether solution of the petroleum vacuum residue is 0.05-0.07 g / mL, the mass concentration of the petroleum ether solution of the template agent is 0.2-0.4 g / mL; the mass concentration of the urea aqueous solution is 0.14-0.42 g / mL; the average particle size of the nano iron oxide is 30-50 nm; the ratio of the petroleum vacuum residue to the template agent is 1:4-1:6; the ratio of the porous carbon to the urea is 1:3-1:7; the preparation pre-annealing condition is to heat up to 700-900°C at a rate of 5°C / min, and the heat preservation time is 100-150 min; the high temperature treatment temperature is 700-900°C, and the heat preservation time is 100-150 min.

7. The preparation method according to claim 4, characterized in that: The reducing atmosphere in step (2) is 5% hydrogen / 95% argon, the reducing temperature is 150-300°C, the reducing time is 1-3h, and the heating rate is 2-10°C / min; the secondary heating temperature is 600-800°C, the holding time is 0.5-2h, and the heating rate is 2-10°C / min.

8. A residual oil derived carbon supported Pt-Co-Au intermetallic compound as claimed in claim 1, a preparation method thereof, and its use in oxygen reduction reaction and as a cathode catalyst for proton exchange membrane fuel cells (PEMFCs).

Citation Information

Cited By

  • ORR multi-metal-doped platinum-based catalyst of fuel cell as well as preparation and application of ORR multi-metal-doped platinum-based catalyst

    CN121528933A